Surface group modification and carrier transport properties of layered transition metal carbides (Ti2CTx, T: –OH, –F and –O). Issue 46 (4th November 2015) - Lai, Shen; Jeon, Jaeho; Jang, Sung Kyu; Xu, Jiao; Choi, Young Jin; Park, Jin-Hong; Hwang, Euyheon; Lee, Sungjoo
Abstract : In spite of recent significant research into various two-dimensional (2D) materials after the emergence of graphene, the development of a new 2D material that provides both high mobility and an appropriate energy band gap (which are crucial for various device applications) remains elusive. Abstract : In spite of recent significant research into various two-dimensional (2D) materials after the emergence of graphene, the development of a new 2D material that provides both high mobility and an appropriate energy band gap (which are crucial for various device applications) remains elusive. In this report, we demonstrate that the carrier transport behaviour of 2D Ti2 CT x, which belongs to the family of 2D transition metal carbides and nitrides, can be tuned by modifying the surface group T x (–OH, –F, and –O). Our results show that 2D Ti2 C(OH) x F y and Ti2 CO x films can be obtained via simple chemical treatment, thermal annealing, and mechanical exfoliation processes. For the first time, we study the carrier transport properties of 2D Ti2 CT x field effect transistors (FETs), obtaining the high field effect carrier mobilities of 10 4 cm 2 V −1 s −1 at room temperature. The temperature dependent resistivity of the Ti2 CO x film exhibits semiconductor like Arrhenius behaviour at zero gate voltage, from which we estimate the energy gap of 80 meV. One interesting feature of the FETs based on transition metal carbides is that the field effect mobility at room temperature is less sensitive to the measured transport gaps, which may arise from the dominant charge transport of activated carriers over the narrow energy gaps of the transition metal carbides. Our results open up the possibility that new 2D materials with high mobilities and appropriate band gaps can be achieved, and broaden the range of electronic device applications of Ti2 CT x films.